PENGARUH PERSONAL BRANDING GREENFLUENCER TERHADAP GREEN PURCHASE BEHAVIOR DENGAN MEDIATOR GREEN TRUST - Nur Bhakti Pertiwi, Widya; Putri Wenang Lusianingrum, Farah; Johan Widikusyanto, Muhammad; Wahyuni Purbohastuti, Arum (Creative Research Management Journal, 2025)
This study aims to analyze the influence of greenfluencer personal branding on green purchase behaviour with green trust as a mediating variable. This research employs a quantitative approach using a survey method. A questionnaire was distributed to 100 respondents across five provinces on the island of Java. Data analysis was conducted using Structural Equation Modelling (SEM) with the AMOS 23 application. Personal branding has a positive effect on green trust. Green trust significantly influences green purchase behaviour. Personal branding does not have a direct effect on green purchase behaviour. Green trust fully mediates the influence of personal branding on green purchase behaviour. This study is limited to the geographic area of Java and the involvement of respondents who follow specific green influencers on Instagram. This research contributes to the fields of green marketing, consumer behaviour, and digital communication, particularly in building green trust through greenfluencer personal branding.